Expression of resistance markers to methotrexate predicts clinical improvement in patients with rheumatoid arthritis. Issue 4 (2nd September 2004) - Wolf, J; Stranzl, T; Filipits, M; Pohl, G; Pirker, R; Leeb, B; Smolen, J S
Abstract : Background: Methotrexate is transported into the cell by the reduced folate carrier (RFC) and out of the cell by members of the multidrug resistance protein family (MRP). Transport proteins may affect the therapeutic efficacy of this drug in patients with rheumatoid arthritis. Objective: To investigate the potential benefit of the presence of RFC and the absence of functional MRP for the efficacy of methotrexate treatment. Methods: The study involved 163 patients (116 female, 47 male; mean age 59.5 years) on methotrexate (mean weekly dose 12.2 mg). RFC was determined using reverse transcriptase polymerase chain reaction, and MRP function by flow cytometry, using a calcein acetoxymethylesther/probenecid assay. Clinical response to methotrexate was evaluated by the EULAR response criteria and the ACR 20% improvement criteria. The clinical data were obtained at the beginning of methotrexate treatment and at the time of blood sampling during ongoing therapy. Patients were divided into four groups according to the presence (+) or absence (−) of RFC and functional (f) MRP. Results: fMRP+/RFC+ and fMRP−/RFC− patients more often had good EULAR response rates (60%, p = 0.014, and 53%, p = 0.035, respectively) in comparison with the fMRP−/RFC+ group (29%); fMRP+/RFC− patients had a low frequency of good disease activity responses. Conclusions: Absence of fMRP plus presence of RFC did not prove to be related to beneficial effects of methotrexate, but the lack or the presence of both fMRP and RFC led to a significantly better therapeutic outcome. Determination of these markers may predict responsiveness to methotrexate.